Unleashing the Power of Options: Profitable Strategies for Nifty Fifty Index Trading - leelavati, T S; Madhavi, S.; Susmitha, K. (Journal of Advanced Research in Service Management, 2023)
A derivative is a contract between two or more parties whose value is based on an agreed-upon underlying financial asset (like a security) or set of assets (like an index). These financial securities are commonly used to access certain markets and may be traded to hedge against risk. The movement of selected investment index whether to rise or fall the instrument. In the investment world, there is an investment instrument called option which gives the investor the choice of investment if the investment instrument goes up by buying call option or if its investment instrument dropped by buying a put option. So investors ignore the rise or fall of underlying assets but rather focus on whether the volatility of the underlying assets has high or low volatility. One of the options strategy is straddle position. The long straddle position strategy indicates that the buyer calls and puts simultaneously at the same exercise price and time period. This means the buyer believes that there will be greater volatility of historical volatility in the investment instrument regardless of the rise or fall of the investment instrument. The present study focuses on the trading of straddles using options. The straddle is purchased when the forecast is positive and sold when negative. Authors considered Nifty Fifty Index as an example, while calculating option strategies.